The clinical burden of extremely preterm birth in a large medical records database in the United States: Mortality and survival associated with selected complications. (August 2022) - Siffel, Csaba; Hirst, Andrew K.; Sarda, Sujata P.; Kuzniewicz, Michael W.; Li, De-Kun
Abstract: Background: Preterm birth is a leading cause of infant mortality, particularly for those born extremely prematurely (EP; <28 weeks' gestational age [GA]). Survivors are predisposed to complications such as bronchopulmonary dysplasia (BPD), chronic lung disease (CLD), intraventricular hemorrhage (IVH), and retinopathy of prematurity (ROP). Aims: To examine the epidemiology, complications, and mortality/survival among EP infants. Study design: Retrospective analysis of electronic medical records from the Kaiser Permanente Northern California database. Subjects: EP infants live-born between 22 and <28 weeks' GA from 1997 to 2016. Outcome measures: Cumulative all-cause mortality/survival were analyzed and stratified by GA (22 to <24, 24 to <26, 26 to <28 weeks), complications (BPD/CLD, IVH, ROP), and birth period (1997 to 2003, 2004 to 2009, 2010 to 2016). Cox proportional hazard models were constructed to assess the mortality risk associated with BPD/CLD or IVH. Results: 2154 EP infants were identified; of these, 916 deaths were recorded. Mortality was highest during the first 3 months (41.7 % cumulative mortality), and few were reported after 2 years (42.5 % cumulative mortality). Mortality decreased with higher GA and over more recent birth periods. BPD/CLD and IVH grade 3/4 were associated with increased mortality risk versus no complications (adjusted hazard ratios 1.41 and 1.78, respectively). Conclusions: The risk of mortality is high during the first few months of life for EP infants, and is even higher for those with BPD and IVH. Despite an overall trend toward increased survival for EP infants, strategies targeting survival of EP infants with these complications are needed. Highlights: Mortality among extremely premature infants was highest during the first 3 months. Mortality decreased with higher gestational age and in more recent years. Bronchopulmonary dysplasia increased the risk of mortality versus no complications. Mortality risk also increased in infants with severe intraventricular hemorrhage.